Knowledge sharing behavior amongst academician: a case study of Universiti Teknologi MARA Kedah campus / Siti Hajjar Mohd Amin, Hazila Timan and Azlyn Ahmad Zawawi - Mohd Amin, Siti Hajjar; Timan, Hazila; Ahmad Zawawi, Azlyn (Research Management Institute, 2012)
Due to the changing business environment, organizations are facing challenges of global competitiveness. Sharing knowledge is an important aspect of most modern organization. University governance is not immune from the impacts of this environmental fluctuation. Universities are creators of new knowledge through research and education but it should not be forgotten that Universities are organizations which will need to utilize knowledge to develop competitive advantage as any other business entity would need to do. This study examines the factors influencing knowledge sharing behavior amongst academicians, taking Universiti Teknologi Mara (UiTM), Kedah as a sample. The factors influencing knowledge sharing behavior include motivation to share knowledge, management support, information technological literacy and teamwork spirit. The result of correlation showed that there is a positive relationship on teamwork spirit and management support toward knowledge sharing behavior amongst academicians.